Eighty Years of Mycopathologia: A Retrospective Analysis of Progress Made in Understanding Human and Animal Fungal Pathogens - Vishnu Chaturvedi; Jean-Philippe Bouchara; Ferry Hagen; Ana Alastruey-Izquierdo; Hamid Badali; Anamelia Lorenzetti Bocca; Jose F. Cano-Lira; Cunwei Cao; Sudha Chaturvedi; Sanjay H. Chotirmall; Anne D. van Diepeningen; Jean-Pierre Gangneux; et al. (Mycopathologia, 2018)

Comparative study on mitogenomes of green tide algae - Chuner Cai; Feng Liu; Ting Jiang; Lingke Wang; Rui Jia; Lingjie Zhou; Kai Gu; Jianfeng Ren; Peimin He (Genetica, 2018)

A new persistent luminescent composite for tracing toxic air particulate matter - Pinghui Ge; Yanjie Liang; Yuan Cheng; Kangning Sun; Rui Liu (Environmental Chemistry Letters, 2018)

Characterization and phylogenetic analysis of the complete maternal mitochondrial genome of freshwater mussel Aculamprotula scripta (Bivalvia: Unionidae: Unioninae) - Rui-Wen Wu; Sa Wang; Yi-Tong Liu; Xiong-Jun Liu; Chun-Hua Zhou; Shan Ouyang; Xiao-Ping Wu (Conservation Genetics Resources, 2018)

Direct and legacy effects of herbivory on growth and physiology of a clonal plant - Bi-Cheng Dong; Mo-Zhu Wang; Rui-Hua Liu; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Biological Invasions, 2018)

Assessing spectral indices to estimate the fraction of photosynthetically active radiation absorbed by the vegetation canopy - Dailiang Peng; Helin Zhang; Le Yu; Mingquan Wu; Fumin Wang; Wenjiang Huang; Liangyun Liu; Rui Sun; Cunjun Li; Dacheng Wang; Fubao Xu (International Journal of Remote Sensing, 2018)

Bacilsubteramide A, a new indole alkaloid, from the deep-sea-derived Bacillus subterraneus 11593 - Chun-Lan Xie; Jin-Mei Xia; Rui-Qiang Su; Jie Li; Yonghong Liu; Xian-Wen Yang; Quan Yang (Natural Product Research, 2018)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Uptake of Urea Nitrogen by Oocystis borgei in Prawn (Litopenaeus vannamei) Aquaculture Ponds - Mei Liu; Xianghu Huang; Rui Zhang; Changling Li; Binhe Gu (Bulletin of Environmental Contamination and Toxicology, 2018)

Role of clouds in accelerating cold‐season warming during 2000–2015 over the Tibetan Plateau - Shan Hua; Yuzhi Liu; Rui Jia; Shuting Chang; Chuqiao Wu; Qingzhe Zhu; Tianbin Shao; Bing Wang (International Journal of Climatology, 2018)
With the global warming slowdown in the twenty‐first century, a huge discrepancy in regional climate warming has been identified over the main region of the Tibetan Plateau (TP). Compared with the +0.04 °C/decade warming from 1961 to 1999, the warming greatly accelerated for the period 2000–2015 at a rate of +0.30 °C/decade. During the same period, warming in the cold season (November to March) was more pronounced than in the warm season (May to September) over the TP. The results also indicated that the middle‐level cloud (middle cloud) decreased (−0.359%/year), while the high‐level cloud (high cloud) increased (+0.241%/year) over almost all the TP during the cold season. Further analysis showed positive net cloud radiative forcing over the western TP from 2000–2015, that is, a heating effect of clouds, especially in the cold season. Combining the trends of the increase in high cloud and the decrease in middle cloud over most parts of the TP, the decreased albedo effect of middle cloud and the increased longwave greenhouse effect of high cloud may have partially contributed to the sustained warming, especially in the cold season from 2000 to 2015. Meanwhile, the results showed that the warming rate and cloud area fraction changes were significantly amplified with elevation. The analysis based on a model of Coupled Model Intercomparison Project Phase 5 shows that the decreased middle cloud plays more important role than the increased high cloud in modulating the enhanced warming over the TP, especially in the cold season.

Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS - Li-Ping Dai; Ling-Xia Zhang; Ya-Lin Liu; Hong Wu; Rui-Xin Liu; Meng Zhao; Shuang-Shuang Tian; Xue Jiang; Sui-Qing Chen (Natural Product Research, 2018)

Acupuncture Prevents the Impairment of Hippocampal LTP Through β1-AR in Vascular Dementia Rats - Ling-Yong Xiao; Xue-Rui Wang; Jing-Wen Yang; Yang Ye; Wen Zhu; Yan Cao; Si-Ming Ma; Cun-Zhi Liu (Molecular Neurobiology, 2018)

Neuregulin-1β Plays a Neuroprotective Role by Inhibiting the Cdk5 Signaling Pathway after Cerebral Ischemia-Reperfusion Injury in Rats - Rui Zhang; Cui Liu; Yaqing Ji; Lei Teng; Yunliang Guo (Journal of Molecular Neuroscience, 2018)

Initial results of centralized autonomous orbit determination of the new-generation BDS satellites with inter-satellite link measurements - Chengpan Tang; Xiaogong Hu; Shanshi Zhou; Li Liu; Junyang Pan; Liucheng Chen; Rui Guo; Lingfeng Zhu; Guangming Hu; Xiaojie Li; Feng He; Zhiqiao Chang (Journal of Geodesy, 2018)

Effects of nitrification inhibitors on gross N nitrification rate, ammonia oxidizers, and N2O production under different temperatures in two pasture soils - Ting Lan; Helen Suter; Rui Liu; Shu Yuan; Deli Chen (Environmental Science and Pollution Research, 2018)

Constitutive expression of antimicrobial peptide PR-39 in transgenic mice significantly enhances resistance to bacterial infection and promotes growth - Fang Zeng; Rui Dong; Chengcheng Zhao; Dewu Liu; Enqin Zheng; Changxu Song; Zhenfang Wu; Zicong Li (Transgenic Research, 2018)

Estimation of the Aerosol Radiative Effect over the Tibetan Plateau Based on the Latest CALIPSO Product - Rui Jia; Yuzhi Liu; Shan Hua; Qingzhe Zhu; Tianbin Shao (Journal of Meteorological Research, 2018)

High-Order Statistics of Temperature Fluctuations in an Unstable Atmospheric Surface Layer over Grassland - Rui Lyu; Fei Hu; Lei Liu; Jingjing Xu; Xueling Cheng (Advances in Atmospheric Sciences, 2018)

Marine green alga Cladophora aokii Yamada and its epiphytes from Yinggehai, Hainan, China: morphological taxonomy, formation and analysis of its environmental adaption - Lanping Ding; Yue Dai; Bingxin Huang; Yongmei Li; Rui Liu; Shaoyang Deng (Acta Oceanologica Sinica, 2018)

An overview of the influence of atmospheric circulation on the climate in arid and semi-arid region of Central and East Asia - Yuzhi Liu; Chuqiao Wu; Rui Jia; Jianping Huang (Science China Earth Sciences, 2018)

Crowdsourcing for forensic disaster investigations: Hurricane Harvey case study - Faxi Yuan; Rui Liu (Natural Hazards, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Nitrogen transformation rates and N2O producing pathways in two pasture soils - Ting Lan; Helen Suter; Rui Liu; Xuesong Gao; Deli Chen (Journal of Soils and Sediments, 2018)

Alzheimer’s Disease Risk Variant rs2373115 Regulates GAB2 and NARS2 Expression in Human Brain Tissues - Guiyou Liu; Tao Wang; Rui Tian; Yang Hu; Zhifa Han; Pingping Wang; Wenyang Zhou; Peng Ren; Jian Zong; Shuilin Jin; Qinghua Jiang (Journal of Molecular Neuroscience, 2018)

Increasing grassland degradation stimulates the non-growing season CO2 emissions from an alpine meadow on the Qinghai–Tibetan Plateau - Lei Ma; Zhisheng Yao; Xunhua Zheng; Han Zhang; Kai Wang; Bo Zhu; Rui Wang; Wei Zhang; Chunyan Liu (Environmental Science and Pollution Research, 2018)

Pyrite textures and compositions from the Zhuangzi Au deposit, southeastern North China Craton: implication for ore-forming processes - Xing-Hui Li; Hong-Rui Fan; Kui-Feng Yang; Pete Hollings; Xuan Liu; Fang-Fang Hu; Ya-Chun Cai (Contributions to Mineralogy and Petrology, 2018)

Precipitation characteristics over the steep slope of the Himalayas in rainy season observed by TRMM PR and VIRS - Yunfei Fu; Xiao Pan; Tao Xian; Guosheng Liu; Lei Zhong; Qi Liu; Rui Li; Yu Wang; Ming Ma (Climate Dynamics, 2018)

The effects of codon usage on the formation of secondary structures of nucleocapsid protein of peste des petits ruminants virus - Xiao-xia Ma; Yi-ning Wang; Xiao-an Cao; Xue-rui Li; Yong-sheng Liu; Jian-hua Zhou; Xue-peng Cai (Genes & Genomics, 2018)

Comparison of stomach microRNA transcriptomes of Tibetan and Yorkshire pigs by deep sequencing - Wen-kui Sun; Yanyue Li; Chi Cheng; Yi-hui Chen; Kai Zeng; Xiaohui Chen; Yiren Gu; Rui Liu; Xuebin Lv; Rong Gao (Genes & Genomics, 2018)

Characterization of clinical features and outcome for human-to-human transmitted severe fever with thrombocytopenia syndrome - Bei Jia; Weihua Wu; Rui Huang; Guiyang Wang; Peixin Song; Yang Li; Yong Liu; Yali Xiong; Xiaomin Yan; Yingying Hao; Juan Xia; Zhaoping Zhang; et al. (Infectious Diseases, 2018)

Fenofibrate ameliorates diabetic retinopathy by modulating Nrf2 signaling and NLRP3 inflammasome activation - Qiuping Liu; Fengjun Zhang; Xian Zhang; Rui Cheng; Jian-xing Ma; Jinglin Yi; Jingming Li (Molecular and Cellular Biochemistry, 2018)

Design, synthesis, and biological evaluation of Cyclobentinib (CB1107) as a potential anti-CML agent - Zijun Zhou; Yang Wang; Jun Li; Baichun Hu; Xiaolin Lin; Ye Chen; Rui Wang; Ju Liu; Hongsheng Liu (Medicinal Chemistry Research, 2018)

AFLP analysis revealed a north to south genetic break in the brown alga Sargassum thunbergii along the coast of China - Juan Liu; Dongmei Zhan; Rui Zhang; Lu Zeng; Gaoge Wang; Zi-Min Hu (Journal of Applied Phycology, 2018)

Low dosage of arsenic trioxide (As2O3) inhibits angiogenesis in epithelial ovarian cancer without cell apoptosis - Dehong Luo; Xiaoyuan Zhang; Renle Du; Wenjuan Gao; Na Luo; Shuangtao Zhao; Yi Li; Rui Chen; Hui Wang; Yonghua Bao; Wancai Yang; Daishun Liu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Review: Water–rock interactions and related eco-environmental effects in typical land subsidence zones of China - Teng Ma; Yao Du; Rui Ma; Cong Xiao; Yanjun Liu (Hydrogeology Journal, 2018)

Structural Strength Analysis of a Tri-Floater Floating Foundation for Offshore VAWT - Liqin Liu; Haixiang Zhao; Wanhai Xu; Rui Yuan; Ying Guo (Journal of Ocean University of China, 2018)

Petrogenesis and Ore Genesis of the Late Yanshanian Granites and Associated Porphyry-Skarn W-Mo Deposits from the Yunkai Area of South China: Evidence from the Zircon U-Pb Ages, Hf Isotopes and Sulfide S-Fe Isotopes - Xinyu Wang; Zhen Yang; Nengsong Chen; Rui Liu (Journal of Earth Science, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Use of Monte Carlo simulation to evaluate the efficacy of tigecycline and minocycline for the treatment of pneumonia due to carbapenemase-producing Klebsiella pneumoniae - Wentao Ni; Guobao Li; Jin Zhao; Junchang Cui; Rui Wang; Zhancheng Gao; Youning Liu (Infectious Diseases, 2018)

Land-use change alters patterns of soil biodiversity in arid lands of northwestern China - Feng-Rui Li; Ji-Liang Liu; Wei Ren; Lu-Lu Liu (Plant and Soil, 2018)

Hydrochemical characteristics and quality assessment of groundwater for irrigation use in central and eastern Songnen Plain, Northeast China - Jianmin Bian; Siyu Nie; Rui Wang; Hanli Wan; Caihong Liu (Environmental Monitoring and Assessment, 2018)

Composition and antimicrobial activity of the essential oil from the branches of Jacaranda cuspidifolia Mart. growing in Sichuan, China - Juanjuan Yuan; Tian Gan; Yingtian Liu; Hui Gao; Weifeng Xu; Tao Zhang; Rui Tan; Zhenghong Cai; Hezhong Jiang (Natural Product Research, 2018)

Clinical characteristics and mutation analysis of five Chinese patients with maple syrup urine disease - Xiaomei Li; Yali Yang; Qing Gao; Min Gao; Yvqiang Lv; Rui Dong; Yi Liu; Kaihui Zhang; Zhongtao Gai (Metabolic Brain Disease, 2018)

RNA Sequence Analysis of Cassava Varieties with High-Starch Content Using De Novo Assembly - Ya-Jing Guo; Xing-Lu Luo; Mao-Gui Wei; Zhao-Liang Liu; Wu-Jing Fan; Rui-Ning Zhai; Yan-Mei Zhu (Journal of Plant Growth Regulation, 2018)

Development of EST-SSR markers derived from transcriptome of Saccharina japonica and their application in genetic diversity analysis - Jing Zhang; Tao Liu; Fengping Rui (Journal of Applied Phycology, 2018)

Transformations of 2-line ferrihydrite and its effect on cadmium adsorption - Yi Huang; Shipeng Zhang; Chao Liu; Huilin Lu; Shijun Ni; Xin Cheng; Zhijie Long; Rui Wang (Environmental Science and Pollution Research, 2018)

Distribution and hydrogeochemical behavior of arsenic enriched groundwater in the sedimentary aquifer comparison between Datong Basin (China) and Kushtia District (Bangladesh) - Md. Enamul Huq; Chunli Su; Shah Fahad; Junxia Li; Most. Sinthia Sarven; Rui Liu (Environmental Science and Pollution Research, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

PCR–DGGE Analysis on Microbial Community Structure of Rural Household Biogas Digesters in Qinghai Plateau - Rui Han; Yongze Yuan; Qianwen Cao; Quanhui Li; Laisheng Chen; Derui Zhu; Deli Liu (Current Microbiology, 2018)

A novel bispecific antibody fusion protein co-targeting EGFR and CD47 with enhanced therapeutic index - Yun Yang; Rui Guo; Qi Chen; Youxun Liu; Pengfei Zhang; Ziheng Zhang; Xi Chen; Tianyun Wang (Biotechnology Letters, 2018)

Genetic diversity and phylogenetic analysis of Aleutian mink disease virus isolates in north-east China - Xue Leng; Dongxu Liu; Jianming Li; Kun Shi; Fanli Zeng; Ying Zong; Yi Liu; Zhibo Sun; Shanshan Zhang; Yadong Liu; Rui Du (Archives of Virology, 2018)

Dietary exposure to cadmium of Shenzhen adult residents from a total diet study - Zhou Wang; Liubo Pan; Guihua Liu; Huimin Zhang; Jinzhou Zhang; Jie Jiang; Ying Xiao; Weibin Bai; Rui Jiao; Wei Huang (Food Additives & Contaminants: Part A, 2018)

Enhanced drought tolerance in tomato plants by overexpression of SlMAPK1 - Liu Wang; Ruirui Zhao; Rui Li; Wenqing Yu; Meijing Yang; Jiping Sheng; Lin Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Atg7-Mediated Autophagy Is Involved in the Neural Crest Cell Generation in Chick Embryo - Guang Wang; En-ni Chen; Chang Liang; Jianxin Liang; Lin-rui Gao; Manli Chuai; Andrea Münsterberg; Yongping Bao; Liu Cao; Xuesong Yang (Molecular Neurobiology, 2018)

Comparative growth increments of gladius surface and cross-sections to estimate Sthenoteuthis oualaniensis age - Xue Feng Wang; Bi Lin Liu; Jian Hua Li; Rui Jiang; Jing Yuan Lin; Teng Li (Marine Biology, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Probing the toxic mechanism of bisphenol A with acid phosphatase at the molecular level - Mengchen Xu; Rui Zhang; Wei Song; Wansong Zong; Rutao Liu (Environmental Science and Pollution Research, 2018)

Soil eaten by chacma baboons adsorbs polar plant secondary metabolites representative of those found in their diet - Chieu Anh Kim Ta; Paula A. Pebsworth; Rui Liu; Stephen Hillier; Nia Gray; John T. Arnason; Sera L. Young (Environmental Geochemistry and Health, 2018)

Photosynthetic response of Bangia fuscopurpurea (Bangiales, Rhodophyta) towards dehydration and hyposalinity - Wen Jun Wang; Zong Gen Shen; Xiu Tao Sun; Fu Li Liu; Zhou Rui Liang; Fei Jiu Wang; Jian Yi Zhu (Biologia, 2018)

U–Pb zircon, geochemical and Sr–Nd–Hf isotopic constraints on age and origin of the intrusions from Wunugetushan porphyry deposit, Northeast China: implication for Triassic–Jurassic Cu–Mo mineralization in Mongolia–Erguna metallogenic belt - Kui-Feng Mi; Zhen-Jiang Liu; Rui-Bin Liu; Chun-Feng Li; Jian-Ping Wang; Run-Min Peng (International Geology Review, 2018)

Ursolic acid, a potential anticancer compound for breast cancer therapy - Ran Yin; Tong Li; Jing Xin Tian; Pan Xi; Rui Hai Liu (Critical Reviews in Food Science and Nutrition, 2018)

Determination of Ocean Tide Loading Displacement by GPS PPP with Priori Information Constraint of NAO99b Global Ocean Tide Model - Hong Zhao; Qin Zhang; Rui Tu; Zhi Liu (Marine Geodesy, 2018)

Geochronology, geochemistry, and Sr–Nd–Pb–Hf isotopes of the Zhunsujihua granitoid intrusions associated with the molybdenum deposit, northern Inner Mongolia, China: implications for petrogenesis and tectonic setting - Xiaojun Zhang; David R. Lentz; Chunliang Yao; Rui Liu; Zhen Yang; Yanxiong Mei; Xianwang Fan; Fei Huang; Ying Qin; Kun Zhang; Zhenfei Zhang (International Journal of Earth Sciences, 2018)

Different behavioral, neural and neuropeptide responses of fathers to their own and to alien pups in mandarin voles - Wei Yuan; Xiang-Ping Yang; Peng Yu; Rui Jia; Fa-Dao Tai; Bin Wei; Xiao Liu; Lei-Ge Ma (Journal of Comparative Physiology A, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Comprehensive drought index as an indicator for use in drought monitoring integrating multi-source remote sensing data: a case study covering the Sichuan-Chongqing region - Tao Ji; Guosheng Li; Hua Yang; Rui Liu; Tairong He (International Journal of Remote Sensing, 2018)

Structure and mechanism of plant histone mark readers - Rui Liu; Xueqin Li; Wei Chen; Jiamu Du (Science China Life Sciences, 2018)

Expression of BpIAA10 from Betula platyphylla (birch) is differentially regulated by different hormones and light intensities - Wendi Xu; Rui Han; Sijia Xu; Jing Jiang; Guifeng Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Up-regulation of FOS-like antigen 1 contributes to neuronal apoptosis in the cortex of rat following traumatic brain injury - Xide Xu; Rui Jiang; Peipei Gong; Qianqian Liu; Yinan Chen; Shiqiang Hou; Debin Yuan; Jiansheng Shi; Qing Lan (Metabolic Brain Disease, 2018)

Periodical drying or no drying during aquaculture affects the desiccation tolerance of a sublittoral Pyropia yezoensis strain - Xiao-lei Li; Wen-jun Wang; Fu-li Liu; Zhou-rui Liang; Xiu-tao Sun; Hai-qing Yao; Fei-jiu Wang (Journal of Applied Phycology, 2018)

A new dimeric diarylpropane from Horsfieldia tetratepala - Shou-Zhen Du; Fang Kuang; Ying Liu; Ye-Gao Chen; Rui Zhan (Natural Product Research, 2018)

Three new polyketides from the marine sponge-derived fungus Trichoderma sp. SCSIO41004 - Xiaoyan Pang; Xiuping Lin; Yongqi Tian; Rui Liang; Junfeng Wang; Bin Yang; Xuefeng Zhou; Kumaravel Kaliyaperumal; Xiaowei Luo; Zhengchao Tu; Yonghong Liu (Natural Product Research, 2018)

Inhibition of two gastric cancer cell lines induced by fucoxanthin involves downregulation of Mcl-1 and STAT3 - Rui-xue Yu; Rui-tao Yu; Zhong Liu (Human Cell, 2018)

Foliar application with nano-silicon reduced cadmium accumulation in grains by inhibiting cadmium translocation in rice plants - Rui Chen; Changbo Zhang; Yanling Zhao; Yongchun Huang; Zhongqi Liu (Environmental Science and Pollution Research, 2018)

Improvement of uridine production in Bacillus subtilis by metabolic engineering - Yanhong Wang; Ranjing Ma; Lu Liu; Lin He; Rui Ban (Biotechnology Letters, 2018)

The higher grain production, the more social deprivation? A case study of Henan province in traditional agricultural areas of China - Jun-bo Gao; Wei-feng Qiao; Yan-sui Liu; Yu-rui Li; Wei Tu; Yong-xian Zhang (Journal of Mountain Science, 2018)

Distribution patterns and population structure of the blue shark ( Prionace glauca ) in the Atlantic and Indian Oceans - Rui Coelho; Jaime Mejuto; Andrés Domingo; Kotaro Yokawa; Kwang‐Ming Liu; Enric Cortés; Evgeny V. Romanov; Charlene da Silva; Fábio Hazin; Freddy Arocha; Aldrin Masawbi Mwilima; Pascal Bach; et al. (Fish and Fisheries, 2018)
The blue shark ( Prionace glauca ) is the most frequently captured shark in pelagic oceanic fisheries, especially pelagic longlines targeting swordfish and/or tunas. As part of cooperative scientific efforts for fisheries and biological data collection, information from fishery observers, scientific projects and surveys, and from recreational fisheries from several nations in the Atlantic and Indian Oceans was compiled. Data sets included information on location, size and sex, in a total of 478,220 blue shark records collected between 1966 and 2014. Sizes ranged from 36 to 394 cm fork length. Considerable variability was observed in the size distribution by region and season in both oceans. Larger blue sharks tend to occur in equatorial and tropical regions, and smaller specimens in higher latitudes in temperate waters. Differences in sex ratios were also detected spatially and seasonally. Nursery areas in the Atlantic seem to occur in the temperate south‐east off South Africa and Namibia, in the south‐west off southern Brazil and Uruguay, and in the north‐east off the Iberian Peninsula and the Azores. Parturition may occur in the tropical north‐east off West Africa. In the Indian Ocean, nursery areas also seem to occur in temperate waters, especially in the south‐west Indian Ocean off South Africa, and in the south‐east off south‐western Australia. The distributional patterns presented in this study provide a better understanding of how blue sharks segregate by size and sex, spatially and temporally, and improve the scientific advice to help adopt more informed and efficient management and conservation measures for this cosmopolitan species.